# Extensions 1→N→G→Q→1 with N=C2×C6 and Q=C3×C12

Direct product G=N×Q with N=C2×C6 and Q=C3×C12
dρLabelID
C62×C12432C6^2xC12432,730

Semidirect products G=N:Q with N=C2×C6 and Q=C3×C12
extensionφ:Q→Aut NdρLabelID
(C2×C6)⋊(C3×C12) = C3×Dic3×A4φ: C3×C12/C6C6 ⊆ Aut C2×C6366(C2xC6):(C3xC12)432,624
(C2×C6)⋊2(C3×C12) = A4×C3×C12φ: C3×C12/C12C3 ⊆ Aut C2×C6108(C2xC6):2(C3xC12)432,697
(C2×C6)⋊3(C3×C12) = C22⋊C4×C33φ: C3×C12/C3×C6C2 ⊆ Aut C2×C6216(C2xC6):3(C3xC12)432,513
(C2×C6)⋊4(C3×C12) = C32×C6.D4φ: C3×C12/C3×C6C2 ⊆ Aut C2×C672(C2xC6):4(C3xC12)432,479
(C2×C6)⋊5(C3×C12) = Dic3×C62φ: C3×C12/C3×C6C2 ⊆ Aut C2×C6144(C2xC6):5(C3xC12)432,708

Non-split extensions G=N.Q with N=C2×C6 and Q=C3×C12
extensionφ:Q→Aut NdρLabelID
(C2×C6).1(C3×C12) = A4×C36φ: C3×C12/C12C3 ⊆ Aut C2×C61083(C2xC6).1(C3xC12)432,325
(C2×C6).2(C3×C12) = C4×C9⋊A4φ: C3×C12/C12C3 ⊆ Aut C2×C61083(C2xC6).2(C3xC12)432,326
(C2×C6).3(C3×C12) = C12×C3.A4φ: C3×C12/C12C3 ⊆ Aut C2×C6108(C2xC6).3(C3xC12)432,331
(C2×C6).4(C3×C12) = C4×C32.A4φ: C3×C12/C12C3 ⊆ Aut C2×C6363(C2xC6).4(C3xC12)432,332
(C2×C6).5(C3×C12) = C4×C32⋊A4φ: C3×C12/C12C3 ⊆ Aut C2×C6363(C2xC6).5(C3xC12)432,333
(C2×C6).6(C3×C12) = C22⋊C4×C3×C9φ: C3×C12/C3×C6C2 ⊆ Aut C2×C6216(C2xC6).6(C3xC12)432,203
(C2×C6).7(C3×C12) = C22⋊C4×He3φ: C3×C12/C3×C6C2 ⊆ Aut C2×C672(C2xC6).7(C3xC12)432,204
(C2×C6).8(C3×C12) = C22⋊C4×3- 1+2φ: C3×C12/C3×C6C2 ⊆ Aut C2×C672(C2xC6).8(C3xC12)432,205
(C2×C6).9(C3×C12) = M4(2)×C3×C9φ: C3×C12/C3×C6C2 ⊆ Aut C2×C6216(C2xC6).9(C3xC12)432,212
(C2×C6).10(C3×C12) = M4(2)×He3φ: C3×C12/C3×C6C2 ⊆ Aut C2×C6726(C2xC6).10(C3xC12)432,213
(C2×C6).11(C3×C12) = M4(2)×3- 1+2φ: C3×C12/C3×C6C2 ⊆ Aut C2×C6726(C2xC6).11(C3xC12)432,214
(C2×C6).12(C3×C12) = M4(2)×C33φ: C3×C12/C3×C6C2 ⊆ Aut C2×C6216(C2xC6).12(C3xC12)432,516
(C2×C6).13(C3×C12) = C3×C6×C3⋊C8φ: C3×C12/C3×C6C2 ⊆ Aut C2×C6144(C2xC6).13(C3xC12)432,469
(C2×C6).14(C3×C12) = C32×C4.Dic3φ: C3×C12/C3×C6C2 ⊆ Aut C2×C672(C2xC6).14(C3xC12)432,470
(C2×C6).15(C3×C12) = C2×C8×He3central extension (φ=1)144(C2xC6).15(C3xC12)432,210
(C2×C6).16(C3×C12) = C2×C8×3- 1+2central extension (φ=1)144(C2xC6).16(C3xC12)432,211
(C2×C6).17(C3×C12) = C22×C4×He3central extension (φ=1)144(C2xC6).17(C3xC12)432,401
(C2×C6).18(C3×C12) = C22×C4×3- 1+2central extension (φ=1)144(C2xC6).18(C3xC12)432,402

׿
×
𝔽